Exploring the Correlation Between Interatomic Bonding and Corrosion Resistance of Metallic Alloys via Combinatorial Method - Liwei Hu; Fucheng Li; Weijie Xie; Chao Wang; Mingxing Li; Gang Wang; Yanhui Liu (Advanced Science)
Abstract Developing metallic alloys with excellent corrosion resistance is of great significance for ensuring the long‐term integrity and reliability of materials in various demanding environments, thereby extending their service life and reducing maintenance costs. However, the corrosion of alloys is a complicated process influenced by many factors, such as composition, structure and surface finishing, and corrosion media. Current evaluations of alloy corrosion resistance involve many steps, which are time‐consuming and laborious to explore within a vast compositional space. In this study, 1874 alloys from 8 alloy systems are prepared and characterized using a combinatorial approach. Analyses of the data indicate that corrosion resistance of an alloy is strongly correlated with metal–metal bond strength (εM–M) and metal–oxygen bond strength (εM–O). Enhanced corrosion resistance can be achieved by alloying elements with high εM–M and εM–O. The consideration from interatomic interactions further reveals that adding elements with high εM–M and εM–O to a base alloy system actually lowers the critical weight‐averaged εM–M and εM–O required for corrosion resistance. The εM–M and εM–O guided selection of alloying elements is applicable in different alloy systems. This finding will facilitate the fast discovery of novel alloys with superior corrosion resistance.